Identification and in vitro functional assessment of 10 CYP2C9 variants found in Chinese Han subjects - Zhang, Qing; Qi, Yuying; Wang, Shuanghu; Zhao, Fangling; Zou, Lili; Zhou, Quan; Geng, Peiwu; Hong, Yun; Yang, Hang; Luo, Qingfeng; Cai, Jianping; Wu, Hualan; et al. (Frontiers in Endocrinology, 2023)
Cytochrome P450 2C9 (CYP2C9) participates in about 15% of clinical drug metabolism, and its polymorphism is associated with individual drug metabolism differences, which may lead to the adverse drug reactions (ADRs). In this study, 1163 Chinese Han individuals were recruited to investigate their distribution pattern of CYP2C9 gene and find out the variants that may affect their drug metabolic activities. We successfully developed a multiplex PCR amplicon sequencing method and used it for the genetic screening of CYP2C9 in a large scale. Besides the wild type CYP2C9*1, totally 26 allelic variants of CYP2C9 were detected, which included 16 previously reported alleles and 10 new non-synonymous variants that had not been listed on the PharmVar website. The characteristics of these newly detected CYP2C9 variants were then evaluated after co-expressing them with CYPOR in S. cerevisiae microsomes. Immunoblot analysis revealed that except for Pro163Ser, Glu326Lys, Gly431Arg and Ile488Phe, most of newly detected variants showed comparable protein expression levels to wild type in yeast cells. Two typical CYP2C9 probe drugs, losartan and glimepiride, were then used for the evaluation of metabolic activities of variants. As a result, 3 variants Thr301Met, Glu326Lys, and Gly431Arg almost lost their catalytic activities and most of other variants exhibited significantly elevated activities for drug metabolism. Our data not only enriches the knowledge of naturally occurring CYP2C9 variants in the Chinese Han population, but also provides the fundamental evidence for its potential clinical usage for personalized medicine in the clinic.